Faktor-Faktor Risiko Mastitis Subklinis pada Kambing Peranakan Etawah di Kabupaten Sleman, Yogyakarta (RISK FACTORS OF SUBCLINICAL MASTITIS ON ETTAWA CROSSBRED GOAT IN SLEMAN REGENCY, YOGYAKARTA) - Suwito, Widodo; Nugroho, Widagdo Sri; Sumiarto, Bambang; Wahyuni, Agnesia Endang Tri Hastuti (Jurnal Veteriner; Vol 15 No 1 (2014), 2014)
In Sleman, a regency in Yogyakarta special region, Etawah crossbred goats are excessively bred for thedairy produce called the goat’s milk. Subclinical mastitis is one of diseases which reduce the yield of goat’smilk. The aim of this study was to determine the risk factors that contribute to the subclinical mastitis onthe Etawah crossbred goats in Sleman. The 200 samples one of which contains 10 mL of goat’s milk weretaken from the udders of the Etawah crossbred goats from the eight goat farms in Sleman. The 200samples were analyzed for the subclinical mastitis using California Mastitis Test (CMT). The data of riskfactors were gathered through a questionnaire. The risk factors on Etawah crossbred goats in Sleman weredetermine with the use of bivariate analysis chi square (X)2, odds ratio (OR) and relative risk (RR). Thegoat’s milk which subclinical mastitis was isolation and identification of bacteria based on biochemicaltests. The risk factors that cause the subclinicall mastitis on Etawah crossbred goats in Sleman were (1)milk yield (X2=14.23; OR=6.52; RR=4.42), (2) age status of lactation (X2=1.60; OR=59.09; RR=17.94), (3)age of weaning (X2=26.06; OR=2.22; RR=1.91), and (4) Body Condition Score (BCS) (X2=13.89; OR=1.29;RR=1.22). Goat’s milk which subclinicall mastitis were isolated  Bacillus sp  (70%), Staphylococcus sp(33%), Pseudomonas sp (29%), Streptococcus sp (25%), Corynebacterium sp (12%), and E. coli (4%).
Keywords: Risk factor, subclinical mastitis, Etawah crossbred goat